1973
DOI: 10.1111/j.1755-3768.1973.tb08251.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Oscillatory Potentials of the Human Electroretinogram in Light and Dark Adaptation

Abstract: The thresholds and the relation to stimulus intensity of the oscillatory potentials and the slow potentials (a-and b-wave) of the human ERG were studied on adaptation to a steady background of different intensities. The total energy and dominant frequency of the oscillatory potentials were calculated by a combined impulse response and Fourier analysis when different intensity of stimulus light was used on adaptation to a maximal background illumination (about 1.5 X 103 photopic cd/m2). The curve of incremental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…The amplitude response of Morlet wavelets found OPs occurring between 25 and 150 ms after stimulus onset, with frequencies in the 70-130 Hz frequency band. Averaged OP data showed trends in OP amplitude and timing that are consistent with previous findings Lachapelle et al, 1991;Wachtmeister, 1972). However, there are changes in amplitude and timing of peak OP that are not characterised by a simple function of flash exposure.…”
Section: Discussionsupporting
confidence: 88%
“…The amplitude response of Morlet wavelets found OPs occurring between 25 and 150 ms after stimulus onset, with frequencies in the 70-130 Hz frequency band. Averaged OP data showed trends in OP amplitude and timing that are consistent with previous findings Lachapelle et al, 1991;Wachtmeister, 1972). However, there are changes in amplitude and timing of peak OP that are not characterised by a simple function of flash exposure.…”
Section: Discussionsupporting
confidence: 88%
“…The oscillatory potentials (OPs) of the electrore-6 tinogram (ERG) reflect rapid adaptational changes and represent neuronal activity in the inner part of the retina (Algvere & Westbeck 1972;Wachtmeister 1972;Wachtmeister & Dowling 1978;Heynen et al 1985). Recently it has been reported that the postnatal development of the OPs generated during relatively more photopic conditions is slower compared to the OPs induced during relatively more scotopic conditions (el Azazi 8c Wachtmeister 1990).…”
mentioning
confidence: 98%
“…Many investigators have studied differences in OPs recorded under either scotopic or photopic conditions, [16][17][18][19][29][30][31][32][33] recorded in response to light stimuli of various colors, 28,[34][35][36] or by using various locations of the active electrode. 37 The fi ndings of some of these studies 18,32,36 suggest that O1 and O2 are generated mostly by cone systems and O3 and O4 mostly by rod systems.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] The aim of this paper is to examine the ways in which retinal adaptation infl uences the behavior of OPs using repeated-fl ash stimuli.…”
mentioning
confidence: 99%